2007
DOI: 10.1093/aje/kwm190
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Adverse Housing and Neighborhood Conditions on the Development of Diabetes Mellitus among Middle-aged African Americans

Abstract: The authors examined the associations of observed neighborhood (block face) and housing conditions with the incidence of diabetes by using data from 644 subjects in the African-American Health Study (St. Louis area, Missouri). They also investigated five mediating pathways (health behavior, psychosocial, health status, access to medical care, and sociodemographic characteristics) if significant associations were identified. The external appearance of the block the subjects lived on and housing conditions were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
91
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(92 citation statements)
references
References 57 publications
1
91
0
Order By: Relevance
“…2,[4][5][6][7]9 Similarly epidemiological studies have shown that noise exposure is associated with self-reported health, 56 depression, 56,57 cardiovascular disease, [58][59][60][61][62] and mortality. 62,63 These associations often persist after adjustment for classic behavioral and biomedical risk factors, suggesting that other factors may partly explain these associations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2,[4][5][6][7]9 Similarly epidemiological studies have shown that noise exposure is associated with self-reported health, 56 depression, 56,57 cardiovascular disease, [58][59][60][61][62] and mortality. 62,63 These associations often persist after adjustment for classic behavioral and biomedical risk factors, suggesting that other factors may partly explain these associations.…”
Section: Discussionmentioning
confidence: 99%
“…1 Those living in disadvantaged neighborhoods are at increased risk of cardiovascular disease and negative mental health outcomes. [2][3][4][5][6][7][8][9] More recently, studies suggest that residents of disadvantaged neighborhoods may also be at greater risk of disturbed sleep. 10 This suggests that effects of neighborhood characteristics on sleep may represent one pathway by which neighborhood environment has an impact on health outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…In past studies, investigators have drawn links between low neighborhood socioeconomic status and obesity (10)(11)(12), hypertension (13,14), diabetes (15), and other associated risk factors, including poor diet (16)(17)(18), infrequent exercise (19,20), and sleep deficiencies (21). In most such studies, researchers relied on self-reported data from respondents, which may lead to bias.…”
mentioning
confidence: 99%
“…19,20 Inflammation may play a role in the relationship between adverse housing/neighborhood conditions and increased risk of diabetes and lower-body functional limitations we have observed in the St. Louis African American Health study. 3,6 Specifically, our adjusted analysis showed that African Americans who lived in neighborhoods with 4 to 5 versus 0 to 1 conditions rated as fair or poor were three times more likely to develop lower-body functional limitations. 3 Also, African Americans who lived in houses rated as fair or poor were more likely to develop diabetes than those living in houses rated as good or excellent.…”
Section: Introductionmentioning
confidence: 89%
“…[1][2][3][4][5][6][7] Only recently has research focused on the mechanisms by which adverse neighborhood and housing conditions affect health and disease outcomes as potential means for targeting interventions in a context-sensitive manner. 8 There are several hypothesized, interrelated, and mediating pathways that could provide such opportunities for intervention, including contextual attributes of place (e.g., availability of grocery stores selling fruits and vegetables), health behavior (e.g., physical activity, alcohol consumption), diseases and conditions (e.g., body mass index (BMI)), and psychosocial factors (e.g., anxiety, stress, and depression).…”
Section: Introductionmentioning
confidence: 99%